The Ghent Altarpiece and the Legend of Saint Christopher - Rogov, Mikhail A. (Actual Problems of Theory and History of Art, 2023)
One of the most important masterpieces of Early Netherlandish painting, the Ghent Altarpiece dates to 1432/35. It was completed by Hubert and Jan van Eyck for the chapel of Joos Vijd and his wife Elisabeth Borluut in the St. John the Cathedral (now St. Bavo’s Cathedral) in Ghent. The purpose of the paper is to introduce into scientific circulation and interpret the image on the Ghent Altarpiece identified by the author. The focus is on the representation of charitable activities of the donors. Specifically, the study examines an image of an episode from the legend of St. Christopher set in a city landscape depicted on the panel XIV of the Ghent Altarpiece (closed view). The methodological basis of the study includes the method of comparative iconographic analysis and is based on the discourse of the social history of art. The iconographic and stylistic analysis of the image found on the inner panel of the Ghent Altarpiece made it possible to clarify its role as possible attribute for denoting the pilgrims’ hospice associated with the activities of the donors. St. Christopher served as the patron saint of the donor’s deceased brother Christoffel, leaving Joos as the only remaining family heir. The donors founded a hospice for pilgrims in Beveren-Waas and the foundation was realized by their heirs after Joos Vijd’s and Elisabeth Borluut’s death (see Buylaert, Verroken, 2019). A detailed analysis revealed two parts of the cityscape separated by a column of biforia, their symbolic contrast is expressed in architecture, behavior of birds, and habitus of pilgrims and townspeople. In the same way, the Madonna of Chancellor Rolin (ca. 1435, Louvre Museum, Paris) shows a hill covered with vineyards right above the hands of Rolin, the Chancellor of Burgundy, who donated one of his best vineyards to the Hospices de Beaune (see Ward, 1994). The technique, repeatedly used by Jan van Eyck to represent donor’s identity, had already been employed in the Ghent Altarpiece. It allows to take a fresh look at the functioning of this polyptych in the context of the social history of art.